(untitled) (American International Journal of Nursing Education and Practice, 2021)
This short communication paper seeks attentions to rethink about the optimum pH range that can create anomalies in aquatic environment and human health. Optimizing pH value is one of the most important task in ranging the physico-chemical parameters especially for surface water quality. Aquatic system of a water body is profoundly dependent on pH range. Presence of free dissolved CO2 which is a vital element for aquatic plants survival that is mostly dependent on water pH range value. In addition, pH range of an aquatic body can influence the O2 availability, water body productivity, stress on fish health and ammonical as well as the metallic toxicity on human health. This short communication suggests that considering a universal optimum pH range for a water body e.g. 6.5-8.5 would not be wise rather this pH optimum range should be considered on the basis of site and water usage variations. JEL Classification Codes: Q53, I12.